Comparison of Surface Properties of Sepiolite and Palygorskite: Surface Energy and Nanoroughness - Almeida, Ricardo O. (2021)
The surface properties of two sepiolite samples and one palygorskite sample were compared using inverse gas chromatography (IGC). Samples were previously conditioned at appropriate temperatures for the removal of all zeolitic water. Dispersive (or Lifshitz-van der Waals) component of the surface energy (γsd), specific interactions (-ΔGas) with π electron donor bases (1-alkenes), and nanomorphology indices (IMχT) based on the injections of cycloalkanes and a branched alkane were measured. From IGC data, at 240 °C, it was found that the palygorskite was clearly distinguished from the sepiolites. The palygorskite possessed a lower γsd, larger -ΔGas with 1-alkenes, and remarkably higher IMχT. Slight differences could also be observed between the two sepiolite samples with the same origin. The results were rationalized in terms of the structural features of the two studied minerals. The larger channels of the sepiolite allow for a better insertion of the n-alkanes (longer retention times) while excluding the bulkier probes, such as cyclooctane or 2,2,4-trimethylpentane. Accordingly, the corresponding γsd values were larger and the IMχT values were lower (higher surface nanoroughness) for the sepiolites. Regarding Lewis acid-base properties, all the sample's surfaces evidenced a very strong amphoteric character. The present results highlight the potential of the evaluated samples for, e.g., adsorption processes with volatile organic compounds or matrix-filler interactions regarding the production of composite structures with Lewis acid-base matrices.